Correlation of blood–brain barrier leakage with cerebral small vessel disease including cerebral microbleeds in Alzheimer's disease - Cheng, Zhaozhao; Dai, Linbin; Wu, Yan; Cao, Yuqin; Chai, Xianliang; Wang, Peng; Liu, Chang; Ni, Ming; Gao, Feng; Wang, Qiong; Lv, Xinyi (Frontiers in Neurology, 2023)
Background: Blood-brain barrier (BBB) damage in AD is usually an important part of its progression, and cerebral small-vessel disease (CSVD) is also a common complication in patients with Alzheimer’s disease (AD). However, the relationship between small cerebrovascular lesions, especially cerebral microbleeds (CMBs), core biomarkers, and the BBB remains controversial. Therefore, our study aimed to investigate the association between cerebral small-vessel damage, especially CMBs, and BBB breakdown and core biomarkers in AD patients. Methods: A total of 139 individuals were divided into probable AD (18F-florbetapir PET positive, n=101) and control groups (cognitively normal, n=38). The levels of cerebrospinal fluid (CSF) and plasma t-tau, p-tau181, Aβ40, Aβ42, and albumin were measured using corresponding commercial assay kits, and the CSF/plasma albumin ratio (Qalb), an indicator of BBB dysfunction, was calculated. CSVD burden and the number of CMBs were defined using magnetic resonance imaging. Results: AD patients had higher Qalb, higher numbers of CMBs, and greater CSVD burden. In both groups, Qalb was associated with higher CSF t-tau. In the AD group, CMBs and CSVD correlated with a higher Qalb, and the numbers of CMBs negatively correlated with CSF Aβ42. Conclusion: BBB damage was accompanied by a more severe CSVD burden and CMB in AD patients, and that CMB was associated with BBB breakdown and amyloid pathology, which may lead to the progression of AD combined with CSVD.